A Patient Developed Painful Muscle Cramps due to Overeating Mangos - Kazuo Abe (Case Reports in Neurological Medicine)
A 79-year-old woman had a habit to eat a mango every night before sleep and experienced muscle cramps during sleep. Her muscle cramps may be resulted from potassium overload due to overeating mangos.